The in-service training of public elementary school teachers in the City of Manila - Tangco, Maura G. 1921- (1955)
A study of the current in-service training practices with the end in view of evaluating the different techniques and their advantages and disadvantages was proposed in this thesis. It specifically sought to determine the demands of the new school upon the teachers, to determine the specific training needs of teachers in service, to analyze the in-service program of the Division of City Schools, to determine the professional, social, and cultural activities of teachers in relation to in-service growth and to present teachers' attitude with regard to in-service training.